Evaluating the growth and cost–benefit analysis of feeding improved indigenous chicken with diets containing black soldier fly larva meal - Waithaka, Mwangi K.; Osuga, Isaac M.; Kabuage, Lucy W.; Subramanian, Sevgan; Muriithi, Beatrice; Wachira, Ann M.; Tanga, Chrysantus M. (Frontiers in Insect Science, 2022)
The high cost of feed has been the major hindrance to a hindrance to the growth, sustainability, profitability, and expansion of poultry production. Black soldier fly larva (BSFL) meal is one of the most promising alternative protein sources widely accepted globally. This study evaluated the growth performance of improved indigenous chicken (IIC)-fed diets containing different inclusion levels of BSFL meals. The BSFL meal inclusion rates included 0% (Diet0), 5% (Diet1), 10% (Diet2), 15% (Diet3), and 20% (Diet4) as replacement to the expensive fish meal in chick and grower diets. Our results showed that diet significantly affected the average daily feed intake, feed conversion ratio, and average daily weight gain of the chicks. The average daily weight gain and feed conversion ratio, except average daily feed intake of the growers, was not significantly affected by diets. The gross profit margin, cost–benefit ratio, and return on investment of feeding birds with BSFL meal varied significantly. The highest cost–benefit ratio of 2.12 was recorded for birds fed on Diet4. Our findings demonstrate that insect-based feeds can successfully and cost-effectively replace fish meal up to 20% without compromising the growth performance of the birds. Therefore, BSFL meal could be incorporated as an essential part of poultry feed production for IIC, potentially reducing the total feed cost while maintaining optimal production and reducing the cost of meat and egg products.